Spherical polyelectrolyte brushes as bio‐platforms to integrate platinum nanozyme and glucose oxidase for colorimetric detection of glucose. Issue 19 (3rd August 2021) - Yang, Qingsong; Li, Li; Sun, Liang; Ye, Zhishuang; Wang, Yunwei; Guo, Xuhong
Abstract: The integration of nanozyme and natural enzyme for cascade reactions has attracted great attention due to their huge potential applications in detection, biomedicine, and catalysis. Here the novel cascade bio‐platforms were fabricated by using spherical poly[(2‐methacryloyloxyethyl)trimethyl ammonium chloride] (PMOTA) brushes (SPB) as nanoreactors to prepare platinum nanoparticles in situ and as nanocarriers to immobilize glucose oxidase (GOX). The generated Pt nanoparticles possess high stability and peroxidase‐like properties, which can catalyze the oxidation of 3, 3′, 5, 5′‐tetramethylbenzidine (TMB) in the presence of H2 O2 to generate blue colored oxidized TMB (oxTMB). And the absorbed GOX can specifically catalyze the oxidation of glucose into gluconic acid and H2 O2, while the produced H2 O2 is subsequently catalyzed by the Pt nanozymes. Thus, the co‐immobilized Pt nanozymes and GOX within SPB (SPB@Pt@GOX) acted as effective biosensors for colorimetric detection of glucose showing high selectivity and great feasibility. This work demonstrates a facile and general strategy to use SPB as bio‐platforms to integrate nanozymes and natural enzymes for cascade reactions. Abstract :